Students’ Problems on Writing Descriptive Text - Ashari, Erwin; Putri, Asa Ismita; Shalehoddin, Shalehoddin (Universitas Negeri Medan, 2024)
The objectives of this researcher was to know the students’ problems in writing descriptive text at first grade of MAN 2 Batam in academic year 2022/2023. This research was descriptive qualitative method. In collecting the data, the researcher did some steps. Researchers preparing the research instrument and giving the test to the students. The data was collected on July at first grade of MAN 2 Batam in academic year 2022/2023. As the subject the researcher took of 33 students. To collect the data, the instrument of this research is test. In analyzing data of the result, the researcher used descriptive analysis. The result of this this research showed the percentage of students’ problems in aspect of organization (18%), content (17%), grammar (18%), mechanics (24%), and vocabulary (23%). Based on the result of the research, it is suggested that the first-grade students of MAN 2 Batam should be given more explanation and exercise in writing descriptive text.